On a Certain Type of Use of Disjunctive Conjunctions in Polish (Compared to Russian) (Slavic Languages Today: Categories, Structures and Processes, 2021)
This article is devoted to semantic interpretation of sentences with coordination which contain a combination of a disjunctive conjunction and an inclusive particle, i.e. syntagmatic groups czy też, czy także, lub też, lub także, albo i, или также, либо и, etc. in contemporary Polish and Russian. As concluded, the particle in such constructions indicates the applicability of the (semantically) composite sentence in relation to the situation in which both terms occur, or implements the additive meaning, indicating the added, complementary character of the second term, or realises the identifying meaning ‘similarly’ compared to the actant outside the coordinate structure, usually from the preceding sentence. The study also examines differences between the functioning of such constructions in Polish and Russian.